Essays on Entrepreneurial Environment: Institutions and Entrepreneurship - Chu, Tuan Vu (Université d'Ottawa / University of Ottawa, 2024)
While discussion of informal institutions received limited attention from entrepreneurship scholars, it remains detached from the broader context of formal institutions. This is partially attributed to the fact that entrepreneurship research is typically conducted within disciplinary boundaries when informal institutions cut across multiple disciplines, requiring multidisciplinary approach and intersection of different bodies of knowledge. Informal institutions, which are deeply rooted in cultural, social, and historical contexts, interact with formal institutions in complex ways. A broad spectrum of perspectives from sociology, psychology, economics, and management offers comprehensive understanding of informal institutions, enabling researchers to delve into these complexities and understand how informal institutions shape entrepreneurial behaviors. Supported by the growing literature on informal institutions and interdisciplinary approaches in entrepreneurship research, the thesis explores how informal institutions can influence the individual intention to embark on entrepreneurial endeavors and how informal practices are employed by firms in the developing economics, which are characterized by underdeveloped institutions. The thesis consists of three individual essays. The first essay discusses the innovation strategies of informal entrepreneurship in the context of imperfect institutional environments. The second essay examines the role of civic engagement in fostering entrepreneurial intention. The third essay explores how religious identity is connected to experiences of eudaimonia that subsequently shapes entrepreneurial intent. These essays draw primarily on two cross-country datasets: The Gallup World Poll and the World Bank Enterprise Survey. While the essays are connected by their focus on the influence of formal and informal institutional environments on entrepreneurship, they provide diverse contributions to a number of influential theories across disciplines. First, the first essay challenges the existing perceptions of "informality costs" incurred by informally created firms and offers alternative insight into their behaviors regarding product introduction in developing countries. The essay also extends contingency theory to the context of formalized firms in developing economies. The second essay builds on the existing framework of self-determination theory to connect civic engagement and entrepreneurial intention. By doing so, it extends pro-social behaviors beyond the context of social entrepreneurship to further encompass entrepreneurial behaviors in a more general sense. Finally, the third essay refines the social identity theory by examining the multifaceted well-being of religious believers. This essay also revises the role of eudaimonic well-being as psychological resources for entrepreneurial intention. The thesis presents important implications for both theory and practice. Theoretically, the thesis uncovers the profound influence of informal institutions on entrepreneurial behaviors through a wide range of disciplinary lenses. Future research may seek to expand upon the novel concepts and relationships introduced and refined in this thesis, laying the groundwork for further exploration and development. Practically, policy makers and organizational institutions would find our findings useful in their quest for building their own strategies of fostering entrepreneurial society.
Keywords: Informal institutions; Informality; Bribery; Innovation; Entrepreneurial intention; Eudaimonic well-being; Religious identity; Religion; Entrepreneurship; Institutional quality; New product introduction; Innovative product introduction; Imitative product introduction